The Impact of Media Literacy and Internet Information Trustworthiness on Fact-Checking Behavior among Elderly Internet Users: The Moderating Role of Critical Thinking - Qiu, Chengyan (International Journal of Social Sciences and Public Administration, 2024)
In the digital age, the spread of misinformation has become a significant concern for individuals and societies worldwide. This study examines the impact of media literacy and the trustworthiness of internet information on fact-checking behavior among retired elderly internet users, with a particular focus on the moderating role of critical thinking. Using a questionnaire survey method, data were collected from 379 retired elderly internet users. The study employs Media Literacy Theory to explore how media literacy and trust in internet information influence the frequency of fact-checking behavior. Results indicate that higher media literacy and trust in internet information are both positively associated with increased fact-checking behavior. Additionally, critical thinking significantly moderates these relationships, enhancing the positive impact of media literacy on fact-checking behavior.